2022
DOI: 10.3389/fpsyg.2022.985604
|View full text |Cite
|
Sign up to set email alerts
|

Psychological contract breach and job performance of new generation of employees: Considering the mediating effect of job burnout and the moderating effect of past breach experience

Abstract: With the intensification of COVID-19 epidemic, it becomes prominent to discuss the issue about the influence of psychological contract breach on job performance of new generation of employees. Based on social exchange theory, fairness theory, and conservation of resource theory, this study constructed a relationship model between psychological contract breach and job performance of new generation of employees with considering the mediating effect of job burnout and the moderating effect of past breach experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, they have not explained the intermediate path, which limits our understanding of effects of work stress. As work stress causes psychological pain to employees, in response, they exhibit lower performance levels (Song et al, 2020 ; Yu et al, 2022 ). Thus, employees' mental health becomes an important path to explain the relationship mechanism between work stress and employee performance, which is revealed in this study using a stress–psychological state–performance framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have not explained the intermediate path, which limits our understanding of effects of work stress. As work stress causes psychological pain to employees, in response, they exhibit lower performance levels (Song et al, 2020 ; Yu et al, 2022 ). Thus, employees' mental health becomes an important path to explain the relationship mechanism between work stress and employee performance, which is revealed in this study using a stress–psychological state–performance framework.…”
Section: Introductionmentioning
confidence: 99%
“…They are well-educated, ambitious, more self-aware and have higher psychological expectations of organisations [9]. However, there is also a growing rift between new-generation employees and the organisation as they are more likely to question the organisation's ability to deliver on its promises and the fairness of the performance reward process [10]. Employees with such beliefs are less likely to trust organisational promises and may no longer be willing to have a long-term employment relationship with their current employer [11] [12].…”
Section: New-generation Employeementioning
confidence: 99%
“…Leaders face challenges in navigating the changing working conditions and fulfilling the PC in the post-COVID-19 world [53,54]. Studies show how the pandemic has influenced the nature of the PC and shifted expectations for both employees and employers [53,[55][56][57][58]. SHRM practitioners play a crucial role in implementing strategies to meet the needs of both parties and ensure stable employment relationships [59].…”
Section: Performance Appraisal and Post-covid-19mentioning
confidence: 99%
“…Existing research has primarily focused on the PC, examining content-based elements (transactional and relational) and evaluation-based elements (fulfillment or breach) [81][82][83]. These studies have explored the impact of psychological contracts on work-related attitudes like job engagement, job involvement, and OC [57,[84][85][86][87]. Coyle-Shapiro and Kessler [88] found that PC fulfillment directly influences employees' affective commitment.…”
Section: Pc and Aocmentioning
confidence: 99%